Giant cell tumor of flexor tendon sheath of little finger: a case report - T. S., Channappa; H. B., Shivakumar; Jhamb, Jai Aditya (International Journal of Research in Orthopaedics, 2019)
Giant cell tumor of the tendon sheath is a benign proliferative lesion of synovial origin that may affect the joints, bursae and tendon sheaths. We report the case of a giant cell tumor of the tendon sheath arising from the flexor tendon sheath of 5th finger of left hand of a 44 year old male patient. The patient underwent ultrasound examination and subsequently magnetic resonance imaging.